LEWIS, Jonathan. 2018. The Algerian War in French/Algerian Writing. Literary Sites of Memory. Cardiff: University of Wales Press - Mertz-Baumgartner, Birgit (apropos [Perspektiven auf die Romania], 2020)
Rezension